2012
DOI: 10.3390/molecules171113045
|View full text |Cite
|
Sign up to set email alerts
|

Sol-gel Entrapped Candida antarctica lipase B — A Biocatalyst with Excellent Stability for Kinetic Resolution of Secondary Alcohols

Abstract: Sol-gel entrapment is an efficient immobilization technique that allows preparation of robust and highly stable biocatalysts. Lipase from Candida antarctica B was immobilized by sol-gel entrapment and by sol-gel entrapment combined with adsorption on Celite 545, using a ternary silane precursor system. After optimization of the immobilization protocol, the best enzyme loading was 17.4 mg/g support for sol-gel entrapped lipase and 10.7 mg/g support for samples obtained by entrapment and adsorption. Sol-gel immo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 35 publications
1
31
0
Order By: Relevance
“…As is widely known, the difficulty of recovering free enzymes from solution and the poor stability of many free enzymes, including Lac, have hindered their development for use in large-scale applications [9]. Accordingly, immobilized enzymes have greater prospects for development since they have higher storage, thermal, and operational stabilities than their free counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…As is widely known, the difficulty of recovering free enzymes from solution and the poor stability of many free enzymes, including Lac, have hindered their development for use in large-scale applications [9]. Accordingly, immobilized enzymes have greater prospects for development since they have higher storage, thermal, and operational stabilities than their free counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25] Previous studies 15,[26][27][28] already stated the versatility of the sol-gel immobilization method and the possibility to ne tune the composition of the binary or ternary precursors mixture to achieve high activity and selectivity, but these studies were carried out on model secondary alcohols (1-phenylethanol or 2-alkanols). The present study demonstrates for the rst time the efficiency of the tailored binary and ternary sol-gel immobilized lipase preparates for the EKR of various heteroaromatic alcohols.…”
Section: 17mentioning
confidence: 99%
“…The immobilization protocols for the sol-gel entrapment of lipases B from Candida antarctica and Pseudomonas uorescens (Amano-AK) were accomplished as previously described (Table 1), with NaF as catalyst for simultaneous hydrolysis and polycondensation (Method 1) 27 or using HCl for the formation of a prepolymer (Method 2). 35 The combined method of sol-gel entrapment and adsorption was also carried out as described elsewhere.…”
Section: Immobilization Of Lipasesmentioning
confidence: 99%
“…It was found that drying under supercritical CO 2 provided higher enzymatic activities and larger pore sizes. Candida antarctica lipase B was sol-gel encapsulated using different protocols and used for the kinetic resolution of secondary alcohols [180]. Lipase from Pseudomonas cepacia was encapsulated in mesoporous silica gels with a moderately hydrophobic microenvironment.…”
Section: Lipasesmentioning
confidence: 99%